THE CHANGES IN THE HUNGARIAN HIGHER EDUCATION SYSTEM DURING THE CHANGE OF REGIME – THE SPREAD OF CHURCH AND FOUNDATION RUN INSTITUTIONS - Csontné Vezendi, Leila; Szűcs, Edit Gizella (Applied Studies in Agribusiness and Commerce, 2025)
This study examines the transformation of the Hungarian higher education system during the change of regime (1989-1990), with particular emphasis on the spread of church- and foundation-run institutions. It presents the legal framework that enabled the establishment of non-state institutions, highlighting Act XXIII of 1990 and subsequent legislation. It uses statistical data to support the significant increase in the number of institutions and students in the non-state sector. It illustrates the different development paths of these institutions through case studies of Károli Gáspár Reformed University and Kodolányi János University. The article analyzes the socio-economic impacts of the changes, including social mobility, economic development, and educational equality. Finally, it reflects on the current challenges and future prospects of Hungarian higher education.